COMT Val158Met Polymorphism, Executive Dysfunction, and Sexual Risk Behavior in the Context of HIV Infection and Methamphetamine Dependence - C. A. Bousman; M. Cherner; J. H. Atkinson; R. K. Heaton; I. Grant; I. P. Everall; The HNRC Group (Interdisciplinary Perspectives on Infectious Diseases)
Catechol-O-methyltransferease (COMT) metabolizes prefrontal cortex dopamine (DA), a neurotransmitter involved in executive behavior; the Val158Met genotype has been linked to executive dysfunction, which might increase sexual risk behaviors favoring HIV transmission. Main and interaction effects of COMT genotype and executive functioning on sexual risk behavior were examined. 192 sexually active nonmonogamous men completed a sexual behavior questionnaire, executive functioning tests, and were genotyped using blood-derived DNA. Main effects for executive dysfunction but not COMT on number of sexual partners were observed. A COMT x executive dysfunction interaction was found for number of sexual partners and insertive anal sex, significant for carriers of the Met/Met and to a lesser extent Val/Met genotypes but not Val/Val carriers. In the context of HIV and methamphetamine dependence, dopaminergic overactivity in prefrontal cortex conferred by the Met/Met genotype appears to result in a liability for executive dysfunction and potentially associated risky sexual behavior.